Working conditions in foundries - A. М. Lazarenkov (Литьë и металлургия)
The factors of the working environment of workplaces determining working conditions of workers in foundries are considered. The excess of permissible levels or concentrations of dust, noise, vibration and other harmful factors in various technological operations of manufacturing castings is resulted.